2022
DOI: 10.3389/fphys.2022.1000547
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effects of biogenic amines on male mating performance in Bactrocera dorsalis

Abstract: In insects, the emergence of mating behavior requires the interplay among sex-determination hierarchy mechanisms that regulate sex-specific differentiation, perception and integration of different sensory cues, and precisely patterned behavioral outputs. Biogenic amines, including octopamine (OA), dopamine (DA), tyramine (TA), serotonin and histamine, have been identified and proposed as putative neurotransmitters, neurohormones and/or neuromodulators in the central nervous system of insects to influence multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Recent studies have revealed that biogenic amines, peptides, odorant‐binding proteins (OBPs), and other genes play important roles in regulating insect courtship and mating. Regarding biogenic amines, among the five types (dopamine, octopamine, tyramine, serotonin, histamine) present in insects, in B. dorsalis , dopamine, and serotonin can promote intermating between males and females, histamine does not affect mating behavior, and octopamine and tyramine might not have a direct effect on male–female mating behavior 128 . Such results have an essential role in revealing the neuromodulatory mechanisms underlying B. dorsalis mating behavior.…”
Section: Tephritidae Reproductive Processesmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have revealed that biogenic amines, peptides, odorant‐binding proteins (OBPs), and other genes play important roles in regulating insect courtship and mating. Regarding biogenic amines, among the five types (dopamine, octopamine, tyramine, serotonin, histamine) present in insects, in B. dorsalis , dopamine, and serotonin can promote intermating between males and females, histamine does not affect mating behavior, and octopamine and tyramine might not have a direct effect on male–female mating behavior 128 . Such results have an essential role in revealing the neuromodulatory mechanisms underlying B. dorsalis mating behavior.…”
Section: Tephritidae Reproductive Processesmentioning
confidence: 94%
“…Regarding biogenic amines, among the five types (dopamine, octopamine, tyramine, serotonin, histamine) present in insects, in B. dorsalis, dopamine, and serotonin can promote intermating between males and females, histamine does not affect mating behavior, and octopamine and tyramine might not have a direct effect on male-female mating behavior. 128 Such results have an essential role in revealing the neuromodulatory mechanisms underlying B. dorsalis mating behavior. For peptides, the reduced expression of sex peptide receptors alters B. oleae ovulation rates.…”
Section: Matingmentioning
confidence: 94%
“…Specific primers were designed for dsRNA synthesis using the T7 promoter sequence, and the T7 RiboMAX Express RNAi System (P1700; Promega, USA) was employed for dsRNA synthesis. After confirming the size of the dsRNA product on a 1.2% agarose gel, the final concentration of dsRNA was adjusted to 3.5 μg/μL and administered via abdominal injection into flies at a dosage of one microgram . Control flies were injected with an equivalent quantity of ds GFP .…”
Section: Methodsmentioning
confidence: 99%
“…After confirming the size of the dsRNA product on a 1.2% agarose gel, the final concentration of dsRNA was adjusted to 3.5 μg/μL and administered via abdominal injection into flies at a dosage of one microgram. 29 Control flies were injected with an equivalent quantity of dsGFP. Subsequently, all flies were maintained under standard rearing conditions (28 °C with 70% relative humidity in a 14:10 h light:dark).…”
Section: Rna Interference Assaymentioning
confidence: 99%
“…In insects, serotonin (5HT) is a key neuromodulator that is linked with the regulation of many behaviors, including feeding 5 , socialization 68 , aggression 9,10 , and mating 11,12 . Food intake is known to be highly dependent on the serotonin levels in the brain of an organism.…”
Section: Introductionmentioning
confidence: 99%